Pre-supplement lithium conductive agent and preparation method and application thereof
By using pre-supplemented lithium conductive agent in lithium-ion batteries, the problems of low efficiency and capacity loss in the first charge and discharge process of lithium-ion batteries are solved, and higher charge and discharge efficiency and capacity are achieved, improving the cycling performance and conductivity of the battery.
Patent Information
- Application Number
- CN202111145020.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-09-28
AI Technical Summary
The positive electrode material conductive agent of existing lithium-ion batteries is relatively low during the first charge and discharge process, resulting in a decrease in capacity loss and energy density. The preparation process of lithium-enhancing conductive agent is complex and the lithium ion removal rate is low.
A pre-complemented lithium conductive agent is proposed, including Li, Li/C and conductive carbon material. Li is attached to the surface of the conductive carbon material, and Li/C is embedded between the layers of the conductive carbon material, and is prepared in an inert atmosphere through high-temperature reaction, providing a new lithium source and diffusion pathway to enhance conductivity.
It improves the first charging and discharging efficiency of lithium-ion batteries, increases the capacity of the positive electrode mixture, improves the battery capacity and circulation performance, and reduces the impedance of the active material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a pre-lithium supplement conductive agent and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the characteristics of high operating voltage, high specific energy, small size, light weight, and long cycle life, making them the focus of competition in the development of the automotive industry. With the continuous development of lithium-ion batteries in the fields of portable electronic devices, electric bicycles and electric vehicles, the requirements for lithium-ion battery performance such as energy density are getting higher and higher.
[0003] Common conductive agents in the positive electrode material formula of lithium-ion batteries mainly include carbon nanotubes, graphene, carbon black, etc., which play a role in enhancing the conductivity of positive electrode materials and reducing the impedance of positive electrodes in batteries. However, the first charge and discharge efficiency of positive electrode materials with conventional conductive agents is about 96%, and the first charge and discharge efficiency of negative electrode materials is only 92-94%, which will cause a certain degree of capacity loss, resulting in a low gram capacity of the positive electrode material mixture of lithium-ion batteries, affecting the energy density of the battery pack. The existing technologies of lithium supplementation of positive electrode active materials, lithium supplementation of positive electrode slurry, and lithium supplementation of oxides and sulfides often have problems such as complex preparation process, low lithium ion release rate, and introduction of other impurities. Therefore, further research is needed. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a pre-supplemented lithium conductive agent and its preparation method and application. The active lithium in the pre-supplemented lithium conductive agent of the present application is easier to be released, has extremely high electrochemical reaction activity, and can effectively make up for the loss of lithium ions during the formation process of the negative electrode SEI film of the lithium ion battery, thereby improving the initial charge and discharge efficiency of the lithium ion battery, increasing the gram capacity of the positive electrode mixture, and increasing the capacity of the lithium ion battery. At the same time, it also improves the cycle performance of the lithium ion battery, and further enhances the conductivity of the conductive agent and reduces the impedance of the active material.
[0005] In one aspect of the present application, the present application proposes a pre-lithium supplement conductive agent. According to an embodiment of the present application, the pre-lithium supplement conductive agent comprises: Li, Li / C and a conductive carbon material, wherein the Li is attached to the surface of the conductive carbon material, and the Li / C is embedded in the interlayer of the conductive carbon material.
[0006] According to the pre-supplemented lithium conductive agent of the embodiment of the present application, firstly, the pre-supplemented lithium conductive agent of the present application provides a new lithium source and lithium ion diffusion pathway for the charging process of the lithium-ion battery, which is used to supplement the loss of lithium ions during the first charge and discharge process, thereby improving the first charge and discharge efficiency of the lithium-ion battery, improving the gram capacity of the positive electrode mixture, improving the capacity of the lithium-ion battery, and also improving the cycle performance of the lithium-ion battery. Secondly, compared with the previous lithium-supplemented conductive agent materials, in the pre-supplemented lithium conductive agent of the present application, since the Li is attached to the surface of the conductive carbon material and the Li / C is embedded in the interlayer of the conductive carbon material, the active lithium in the pre-supplemented lithium conductive agent is easier to come out, has extremely high electrochemical reaction activity, can effectively supplement the loss of active substances during the first charge and discharge process, and does not introduce other impurities. Again, compared with conventional conductive materials, in the pre-lithium conductive agent of the present application, since the Li is attached to the surface of the conductive carbon material and the Li / C is embedded in the interlayer of the conductive carbon material, there are more heteroatomic interfaces between the Li atoms and the C atoms, which is beneficial to electron transfer, further enhancing the conductivity of the conductive agent, thereby reducing the impedance of the active material.
[0007] In addition, the pre-lithium conductive agent according to the above embodiment of the present application may also have the following additional technical features:
[0008] In some embodiments of the present application, based on the total mass of the Li, the Li / C and the conductive carbon material, the total content of the Li and the Li / C is 22-68 wt %.
[0009] In some embodiments of the present application, based on the total mass of the Li and the Li / C, the content of the Li / C is 5-30 wt %.
[0010] In some embodiments of the present application, the specific surface area of the pre-supplemented lithium conductive agent is 510-515 g / m 2 .
[0011] In some embodiments of the present application, the conductive carbon material is selected from at least one of nanotubes, graphene, carbon black and carbon fibers.
[0012] In another aspect of the present application, the present application proposes a method for preparing the above-mentioned pre-lithium conductive agent. According to an embodiment of the present application, the method comprises:
[0013] mixing lithium powder and a conductive carbon material to obtain a mixture;
[0014] The mixture is reacted at high temperature in an inert atmosphere to obtain a pre-supplemented lithium conductive agent.
[0015] According to the method for preparing the above-mentioned pre-replenishment of lithium conductive agent according to the embodiment of the present application, compared with the previous conductive agent lithium replenishment technology, the method adopts a simple direct heating method, which can quickly replenish the conductive agent lithium under inert atmosphere and high temperature conditions, wherein some free lithium atoms enter the lattice of interlayer carbon atoms to form Li / C, and the remaining elemental Li is attached to the surface of the conductive carbon material, and no other impurities are introduced in the preparation process. The active lithium in the pre-replenishment of lithium conductive agent prepared in this way is easier to escape, has extremely high electrochemical reaction activity, and can effectively make up for the loss of lithium ions during the formation process of the negative electrode SEI film of the lithium ion battery, thereby improving the initial charge and discharge efficiency of the lithium ion battery, improving the gram capacity of the positive electrode mixture, and improving the capacity of the lithium ion battery. At the same time, it also improves the cycle performance of the lithium ion battery, and further enhances the conductivity of the conductive agent and reduces the impedance of the active material.
[0016] In addition, the method according to the above embodiment of the present application may also have the following additional technical features:
[0017] In some embodiments of the present application, the mass ratio of the lithium powder to the conductive carbon material is 1:(0.5-4), preferably 1:(2-3).
[0018] In some embodiments of the present application, the temperature of the high temperature reaction is 600-800°C.
[0019] In some embodiments of the present application, the high temperature reaction time is 5-8 hours.
[0020] In some embodiments of the present application, the inert atmosphere is a nitrogen atmosphere, a helium atmosphere, or an argon atmosphere.
[0021] In the third aspect of the present application, the present application proposes a positive electrode sheet. According to an embodiment of the present application, the positive electrode sheet is prepared by using the above-mentioned pre-supplemented lithium conductive agent or the pre-supplemented lithium conductive agent obtained by the above-mentioned preparation method. Therefore, the positive electrode sheet has all the advantages of the pre-supplemented lithium conductive agent in the above-mentioned embodiment.
[0022] In the fourth aspect of the present application, the present application proposes a negative electrode sheet. According to an embodiment of the present application, the negative electrode sheet is prepared by using the above-mentioned pre-supplemented lithium conductive agent or the pre-supplemented lithium conductive agent obtained by the above-mentioned preparation method. Therefore, the positive electrode sheet has all the advantages of the pre-supplemented lithium conductive agent in the above-mentioned embodiment.
[0023] In a fifth aspect of the present application, the present application provides a lithium-ion battery. According to an embodiment of the present application, the lithium-ion battery has the above-mentioned positive electrode sheet. As a result, the initial coulombic efficiency and gram capacity of the lithium-ion battery are improved, and the cycle performance of the lithium-ion battery is improved.
[0024] In the sixth aspect of the present application, the present application proposes an electric vehicle. According to an embodiment of the present application, the electric vehicle has a lithium-ion battery as described above. As a result, the vehicle equipped with the lithium battery has excellent endurance, thereby meeting the use needs of consumers.
[0025] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0026] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are intended to be used to explain the present application, but should not be construed as limiting the present application.
[0027] In one aspect of the present application, a pre-supplement lithium conductive agent is proposed. According to an embodiment of the present application, the pre-supplement lithium conductive agent includes: Li, Li / C and a conductive carbon material, wherein the Li is attached to the surface of the conductive carbon material in the form of particles, and the Li / C is embedded in the interlayer of the conductive carbon material in the form of particles. Therefore, firstly, the pre-supplement lithium conductive agent of the present application provides a new lithium source and lithium ion diffusion pathway for the charging process of the lithium-ion battery, which is used to supplement the loss of lithium ions during the first charge and discharge process, thereby improving the first charge and discharge efficiency of the lithium-ion battery, increasing the gram capacity of the positive electrode mixture, increasing the capacity of the lithium-ion battery, and also improving the cycle performance of the lithium-ion battery. For example, the active material of a traditional lithium iron phosphate battery is only lithium iron phosphate particles. During the charging process of the battery, the lithium iron phosphate particles serve as the only lithium source. The main diffusion pathways of lithium ions include the solid-phase diffusion of lithium ions inside the lithium iron phosphate particles and the liquid-phase diffusion of lithium ions in the electrolyte after the lithium ions are detached from the surface of the lithium iron phosphate particles. After the pre-supplemented lithium conductive agent of the present application is adopted, during the first charging process of the lithium iron phosphate battery, the pre-supplemented lithium conductive agent can provide lithium ions to the negative electrode to supplement the loss of lithium ions during the first charge and discharge process. Secondly, compared with the previous lithium supplement conductive agent materials, in the pre-supplemented lithium conductive agent of the present application, since the Li is attached to the surface of the conductive carbon material and the Li / C is embedded in the interlayer of the conductive carbon material, the active lithium in the pre-supplemented lithium conductive agent is easier to be released, has extremely high electrochemical reaction activity, can effectively supplement the loss of active materials during the first charge and discharge process, and does not introduce other impurities. Again, compared with conventional conductive materials, in the pre-lithium conductive agent of the present application, since the Li is attached to the surface of the conductive carbon material and the Li / C is embedded in the interlayer of the conductive carbon material, there are more heteroatomic interfaces between the Li atoms and the C atoms, which is conducive to electron transfer, further enhancing the conductivity of the conductive agent, thereby reducing the impedance of the active material.
[0028] According to a specific embodiment of the present application, based on the total mass of the Li, the Li / C and the conductive carbon material, the total content of the Li and the Li / C is 22-68wt%. Thus, the total content of the Li and the Li / C is limited to the above range, ensuring the content of the Li attached to the surface of the conductive carbon material and the content of the Li / C embedded in the interlayer of the conductive carbon material, so that the content is sufficient to supplement the loss of lithium ions during the first charge and discharge process, thereby improving the first charge and discharge efficiency of the lithium-ion battery, improving the gram capacity of the positive electrode mixture, and improving the capacity of the lithium-ion battery. At the same time, it also improves the cycle performance of the lithium-ion battery. The inventor found that if the total content of the Li and the Li / C is too little, it will cause its content to be insufficient to supplement the loss of lithium ions during the first charge and discharge process, thereby failing to improve the first charge and discharge efficiency of the lithium-ion battery; if the total content of the Li and the Li / C is too much, some Li particles will be free outside the conductive carbon material to form large-sized agglomerates.
[0029] According to another specific embodiment of the present application, based on the total mass of the Li and the Li / C, the content of the Li / C is 5-30wt%. Thus, the content of the Li / C embedded in the conductive carbon material layer is limited to the above range, and a conductive agent material with good lithium supplementation effect is further obtained. The inventors found that if the content of the Li / C embedded in the conductive carbon material layer is too little, the Li atoms may not be able to effectively open the carbon layer spacing of the conductive carbon material, resulting in the obstruction of lithium ion transmission between the carbon layers; if the content of the Li / C is too much, it will cause too many metal lithium particles to hinder the transmission of lithium ions, and also cause the impedance of the active material to increase.
[0030] According to another specific embodiment of the present application, the specific surface area of the pre-supplemented lithium conductive agent is 510-515 g / m 2 , which further facilitates the full contact between the pre-lithium conductive agent and the active material, thereby reducing the impedance of the active material. It should be noted that compared with the conductive carbon material, the specific surface area of the pre-lithium conductive agent is slightly increased, and its surface area increases by about 2-3% after lithium replenishment.
[0031] In the embodiments of the present application, the specific type of the above-mentioned conductive carbon material is not particularly limited, and those skilled in the art can choose it at will according to actual needs. As a preferred solution, the conductive carbon material is selected from at least one of nanotubes, graphene, carbon black and carbon fiber.
[0032] In another aspect of the present application, the present application proposes a method for preparing the above-mentioned pre-lithium conductive agent. According to an embodiment of the present application, the method comprises:
[0033] The lithium powder and the conductive carbon material are mixed to obtain a mixture; the mixture is reacted at a high temperature in an inert atmosphere to obtain a pre-lithium supplemented conductive agent.
[0034] In this step, under inert atmosphere and high temperature conditions, some free lithium atoms enter the lattice of interlayer carbon atoms to form Li / C, and the Li / C is embedded in the interlayer of the conductive carbon material in the form of particles (scattered distribution), and the remaining elemental Li is attached to the surface of the conductive carbon material in the form of particles (scattered distribution), without significantly changing the morphology of the conductive carbon material.
[0035] According to a specific embodiment of the present application, the mass ratio of the lithium powder and the conductive carbon material is 1: (0.5-4), preferably 1: (2-3), thereby limiting the mass ratio of the lithium powder and the conductive carbon material to the above range, ensuring the content of Li attached to the surface of the conductive carbon material and the content of Li / C embedded in the interlayer of the conductive carbon material, so that the content is sufficient to supplement the loss of lithium ions during the first charge and discharge process, thereby improving the first charge and discharge efficiency of the lithium-ion battery, improving the gram capacity of the positive electrode mixture, and improving the capacity of the lithium-ion battery. The inventors found that if the content of the lithium powder is too little, the total content of the Li and the Li / C will be insufficient to supplement the loss of lithium ions during the first charge and discharge process, thereby failing to improve the first charge and discharge efficiency of the lithium-ion battery; if the content of the lithium powder is too much, the total content of the Li and the Li / C will be too much, thereby causing the Li particles to be free outside the conductive carbon material to form large-sized agglomerates.
[0036] According to another specific embodiment of the present application, the temperature of the high temperature reaction is 600-800°C. Therefore, the temperature of the high temperature reaction is limited to the above range to effectively form the Li&Li / C@A composite material, wherein A represents a conductive carbon material. The inventors found that if the reaction temperature is too low, it will cause the inability to form free lithium atoms, thereby causing the inability to allow the free lithium atoms to enter the lattice of the interlayer carbon atoms to form Li / C, and thus the inability to form the Li&Li / C@A composite material; If the reaction temperature is too high, the conductive carbon material will be carbonized and decomposed, thereby failing to form the Li&Li / C@A composite material.
[0037] According to another specific embodiment of the present application, the high temperature reaction time is 5-8h, thus, the high temperature reaction time is limited to the above range, so that the mass ratio of Li attached to the surface of the conductive carbon material and Li / C embedded in the interlayer of the conductive carbon material is maintained within a suitable range. The inventors found that if the reaction time is too short, too few free lithium atoms will enter the lattice of the interlayer carbon atoms, resulting in too little Li / C being formed; if the reaction time is too long, the conductive agent material may decompose.
[0038] In the embodiments of the present application, the specific type of the inert atmosphere is not particularly limited, and those skilled in the art can select it at will according to actual needs. As a preferred solution, the inert atmosphere is a nitrogen atmosphere, a helium atmosphere, or an argon atmosphere. Thus, the inert atmosphere of the above type can prevent the conductive carbon material from being oxidized in the presence of oxygen at high temperature, and the inert atmosphere of the above type also has the advantage of being stable at high temperatures.
[0039] According to the method for preparing the above-mentioned pre-replenishment of lithium conductive agent according to the embodiment of the present application, compared with the previous conductive agent lithium replenishment technology, the method adopts a simple direct heating method, which can quickly replenish the conductive agent lithium under inert atmosphere and high temperature conditions, wherein some free lithium atoms enter the lattice of interlayer carbon atoms to form Li / C, and the remaining elemental Li is attached to the surface of the conductive carbon material, and no other impurities are introduced in the preparation process. The active lithium in the pre-replenishment of lithium conductive agent prepared in this way is easier to escape, has extremely high electrochemical reaction activity, and can effectively make up for the loss of lithium ions during the formation process of the negative electrode SEI film of the lithium ion battery, thereby improving the initial charge and discharge efficiency of the lithium ion battery, improving the gram capacity of the positive electrode mixture, and improving the capacity of the lithium ion battery. At the same time, it also improves the cycle performance of the lithium ion battery, and further enhances the conductivity of the conductive agent and reduces the impedance of the active material.
[0040] In the third aspect of the present application, the present application proposes a positive electrode sheet. According to an embodiment of the present application, the positive electrode sheet is prepared by using the above-mentioned pre-supplemented lithium conductive agent or the pre-supplemented lithium conductive agent obtained by the above-mentioned preparation method. Therefore, the positive electrode sheet has all the advantages of the pre-supplemented lithium conductive agent in the above-mentioned embodiment.
[0041] In the fourth aspect of the present application, the present application proposes a negative electrode sheet. According to an embodiment of the present application, the negative electrode sheet is prepared by using the above-mentioned pre-supplemented lithium conductive agent or the pre-supplemented lithium conductive agent obtained by the above-mentioned preparation method. Therefore, the positive electrode sheet has all the advantages of the pre-supplemented lithium conductive agent in the above-mentioned embodiment.
[0042] In a fifth aspect of the present application, the present application provides a lithium-ion battery. According to an embodiment of the present application, the lithium-ion battery has the above-mentioned positive electrode sheet. As a result, the initial coulombic efficiency and gram capacity of the lithium-ion battery are improved, and the cycle performance of the lithium-ion battery is improved.
[0043] In the sixth aspect of the present application, the present application proposes an electric vehicle. According to an embodiment of the present application, the electric vehicle has a lithium-ion battery as described above. As a result, the vehicle equipped with the lithium battery has excellent endurance, thereby meeting the use needs of consumers.
[0044] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0045] Example 1
[0046] In a nitrogen environment, 0.4 g lithium powder and 0.8 g carbon nanotubes were fully mixed and pyrolyzed in a nitrogen atmosphere at 600° C. for 6 hours to prepare a Li&Li / C@CNTs-1:2 composite material.
[0047] Example 2
[0048] In a nitrogen environment, 0.4 g lithium powder and 0.8 g graphene were fully mixed and pyrolyzed at 700 °C in a nitrogen atmosphere for 7 hours to prepare the Li&Li / C@rGO-1:2 composite material.
[0049] Example 3
[0050] In a nitrogen environment, 0.4 g lithium powder and 0.8 g carbon black were fully mixed and pyrolyzed at 800° C. in a nitrogen atmosphere for 5 hours to prepare a Li&Li / C@C-1:2 composite material.
[0051] Example 4
[0052] The preparation method was the same as that in Example 1, except that the addition ratio of lithium powder and carbon nanotubes was changed, and 0.2 g lithium powder and 0.8 g carbon black were added and mixed to prepare a Li&Li / C@CNTs-1:4 composite material.
[0053] Example 5
[0054] The preparation method was the same as that in Example 1, except that the addition ratio of lithium powder and carbon nanotubes was changed, and 0.6 g lithium powder and 0.3 g carbon black were added and mixed to prepare a Li&Li / C@CNTs-1:0.5 composite material.
[0055] Comparative Example 1
[0056] 2 g of lithium orthosilicate and 0.2 g of sucrose were mixed evenly, transferred to a tube furnace and sintered at 600° C. in an inert atmosphere for 6 hours to prepare a silicate composite lithium supplement.
[0057] Comparative Example 2
[0058] In a nitrogen environment, 0.4 g of lithium powder and 0.8 g of carbon nanotubes were fully mixed and pyrolyzed in a nitrogen atmosphere at 500° C. for 6 hours, but no lithium-carbon composite conductive electrode material was obtained.
[0059] Comparative Example 3
[0060] In a nitrogen environment, 0.4 g lithium powder and 0.8 g carbon nanotubes were fully mixed and pyrolyzed in a nitrogen atmosphere at 900° C. for 6 hours. The carbon content of the obtained material was significantly reduced and the lithium particles were agglomerated.
[0061] The lithium-supplementing conductive agents prepared in Examples 1-5 and Comparative Example 1 were mixed with lithium iron phosphate, PVDF, and carbon black to prepare slurries, and the slurries were coated on aluminum foils, respectively, and the positive electrodes were prepared by baking and rolling. The negative electrode graphite material was mixed with carbon black, a binder (specifically a mixture of CMC (sodium carboxymethyl cellulose) and styrene-butadiene rubber (SBR)) and a solvent to obtain a negative electrode slurry; the negative electrode slurry was coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained by baking and rolling. The positive electrode sheet and the negative electrode sheet were assembled into a battery with a designed battery capacity of 1.80Ah. The longitudinal resistivity test was performed on the positive electrode sheet, and the battery was subjected to capacity division, DCIR, and 45°C 0.5C / 0.5C test cycle tests. The test results are shown in Table 1.
[0062] Table 1
[0063]
[0064] By comparing Example 1 with Examples 4-5, it can be seen that the lithium-carbon mass ratio of the product can be controlled by adjusting the mass ratio of lithium powder and conductive carbon material. Compared with Li&Li / C@CNTs-1:4 and Li&Li / C@CNTs-1:0.5, the Li&Li / C@CNTs-1:2 composite material of Example 1 has better conductivity. The electrochemical test results show that compared with other examples, the Li&Li / C@CNTs-1:2 pre-supplemented lithium conductive agent material prepared in Example 1 has lower resistivity (30Ω*cm) and DC internal resistance (97.6mΩ), higher mixed material gram capacity (138.83mAh / g) and higher 500-cycle cycle capacity retention rate (98.1%), and its electrochemical performance is better than the pre-supplemented lithium conductive agent material prepared in other examples. The main reason is that the amount of lithium embedded is too small to open the carbon layer spacing, so that the transmission of lithium ions between carbon layers is hindered. When the lithium is embedded in excess, the metal particles will hinder the transmission of lithium ions and increase the impedance.
[0065] By comparing Examples 1-5 and Comparative Example 1, it can be seen that the use of lithium orthosilicate for pre-replenishing lithium in Comparative Example 1 not only introduces impurities, but also the pre-replenishing lithium conductive agent material prepared in Comparative Example 1 has a higher resistivity (39Ω*cm) and DC internal resistance (98.90mΩ), a lower mixed material gram capacity (136.59mAh / g) and a lower 500-cycle capacity retention rate (97.7%), and its electrochemical performance is inferior to the pre-replenishing lithium conductive agent materials prepared in other embodiments.
[0066] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0067] Although the embodiments of the present application have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present application. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present application.
Claims
1. A method for preparing a pre-lithium conductive agent, characterized in that: include: mixing lithium powder and a conductive carbon material to obtain a mixture; In an inert atmosphere, reacting the mixture at a high temperature to obtain a pre-supplemented lithium conductive agent; During the high temperature reaction, some of the free lithium atoms enter the lattice of the interlayer carbon atoms to form Li / C; The temperature of the high temperature reaction is 600-800°C, and the time of the high temperature reaction is 5-8h. The mass ratio of the lithium powder to the conductive carbon material is 1:(2-3); The pre-lithium conductive agent comprises: Li, Li / C and a conductive carbon material, wherein the Li is attached to the surface of the conductive carbon material, and the Li / C is embedded in the interlayer of the conductive carbon material. Based on the total mass of the Li, the Li / C and the conductive carbon material, the total content of the Li and the Li / C is 22-68wt%, Based on the total mass of the Li and the Li / C, the content of the Li / C is 5-30 wt %.
2. The method according to claim 1, characterized in that The specific surface area of the pre-supplemented lithium conductive agent is 510-515 g / m 2 .
3. The method according to claim 1, characterized in that: The conductive carbon material is selected from at least one of nanotubes, graphene, carbon black and carbon fibers.
4. The method according to any one of claims 1 to 3, characterized in that: The inert atmosphere is a nitrogen atmosphere, a helium atmosphere or an argon atmosphere.
5. A positive electrode sheet, characterized in that: The positive electrode sheet is prepared by using the pre-lithium-supplemented conductive agent prepared by the method described in any one of claims 1 to 4.
6. A negative electrode sheet, characterized in that: The negative electrode sheet is prepared by using the pre-lithium-supplemented conductive agent prepared by the method described in any one of claims 1 to 4.
7. A lithium ion battery, characterized in that: A positive electrode sheet according to claim 5 and / or a negative electrode sheet according to claim 6.
8. An electric vehicle, characterized in that: A lithium ion battery according to claim 7.
Citation Information
Patent Citations
Lithium-carbon composite, preparation method and application thereof as well as lithium compensation method
CN107305941A